The Problem of Transnational Corporation’s Legal Personality in the International Law Doctrine - M. R. Berandze (Московский журнал международного права, 2009)
The intensifying international relations have affected changes, increase, and creation of new kinds of commercial interaction forms by multinational structures. For years, legal science have been seeking legal instruments, regulating international commercial relations. With the undergoing change and complexity of forms, subjects and objects, the international relations are not regulated neither by international law, nor national law. Thus, the problem of searching the new legal mechanisms, sufficient for legal regulation of the international relations, appears.The American international law doctrine, in the person of Philip C. Jessup, found a theory of “transnational law”. Due to the increasing impact of international economic relations and with the growing role of transnational corporations this theory has evolved. The main conclusion of the article is that the circle of international law subjects should not be expanded arbitrarily. Mainly, it should be noticed in view of the jurists’ attempts to provide legal entities with international legal personality.